It's a fabulous life : a novel - Farmer, Kelly (Alcove Press, 2023)
"After years of putting aside her dreams of travel and adventure, Bailey George is ready to leave Lanford Falls and her responsibilities behind on a long-awaited vacation to New York City. But when the volunteer who took over her leadership position for the town's Winter Wonderfest has a medical emergency, Bailey finds herself stuck in Lanford Falls. She gets roped into reassuming her old role, not wanting to let the town or her friends and family down. Staying home seems slightly less terrible when Bailey runs into her high school crush, Maria Hatcher. A kiss they shared years ago in the town's mistletoe grove was a life-defining moment for them both. Maria quickly offers to pitch in and help with Winter Wonderfest. Her sunny disposition and holiday cheer perk up Bailey's grinchy feelings about everything. However, one disaster after another snowball on the day of the festival. Bailey's frustration boils over, and she ends up on the town's old wooden bridge. There, she meets fabulous drag queen Clara Angel. Bailey declares that she wishes she hadn't been born in this Christmas-obsessed, suffocating small town. With a little of the magic Clara possesses, she shows Bailey how wrong she is about Lanford Falls and her place in it. And that with a little hope and some true holiday spirit, there is a way to attain all her dreams."--